24(S),25-Epoxycholesterol and cholesterol 24S-hydroxylase (CYP46A1) overexpression promote midbrain dopaminergic neurogenesis in vivo - Spyridon Theofilopoulos (Journal of Biological Chemistry, 2019)
The liver X receptors Lxrα/NR1H3 and Lxrβ/NR1H2 are ligand-dependent nuclear receptors critical for midbrain dopaminergic (mDA) neuron development. We previously found that 24(S),25-epoxycholesterol (24,25-EC), the most potent and abundant Lxr ligand in the developing mouse midbrain, promotes mDA neurogenesis in vitro. In this study, we demonstrate that 24,25-EC promotes mDA neurogenesis in an Lxr-dependent manner, in the developing mouse midbrain in vivo and also prevents toxicity induced by the Lxr inhibitor geranylgeranyl pyrophosphate. Furthermore, using MS we show that overexpression of human cholesterol 24S-hydroxylase (CYP46A1) increases the levels of both 24(S)-hydroxycholesterol (24-HC) and 24,25-EC in the developing midbrain, resulting in a specific increase in mDA neurogenesis in vitro and in vivo, but has no effect on occulomotor or red nucleus neurogenesis. 24-HC, unlike 24,25-EC, did not affect in vitro neurogenesis, indicating that the neurogenic effect of 24,25-EC on mDA neurons is specific. Combined, our results indicate that increased levels of 24,25-EC in vivo, by intracerebroventricular delivery in wild-type mice or by overexpression of its biosynthetic enzyme CYP46A1, specifically promote mDA neurogenesis. We propose that increasing the levels of 24,25-EC in vivo may be a useful strategy to combat the loss of mDA neurons in Parkinson’s disease.